Avaliação de métodos de decomposição de grafite flexível para determinação de elementos traço por ICP OES - Balestrin, Paula (2014)
In this work different methods of sample preparation were evaluated for flexible graphite digestion. Dry ashing decomposition, microwave-assisted wet digestion (MAWD) and microwave-induced combustion (MIC) were applied for further determination of Ag, As, Cd, Ga, In, Pb and Zn by inductively coupled plasma optical emission spectrometry (ICP OES). The dry ashing method allowed a complete decomposition of flexible graphite with temperature of 1000 °C for 4 hours. However, due to the high temperature used, quantitative recoveries were not obtained for all analytes and thus this method was not considered suitable for decomposition of flexible graphite. Regarding the method of MAWD, high amount of insoluble residue was observed after the decomposition procedure using 100 mg of flexible graphite and HNO3 14 mol L-1. This method was also considered unsuitable for the decomposition of flexible graphite samples. For the MIC method, efficient decomposition were obtained when 100 mg of sample and 300 mg of microcrystalline cellulose in the pellet form were used. The cellulose was used as an auxiliary combustion agent for the decomposition of flexible graphite. For MIC an efficient decomposition was obtained by the use of diluted HNO3 (4 mol L-1) absortion solution and allowed recoveries greater than 90% for all analytes. Additionally, certified reference material of coal (BCR 40 - Trace elements in a coal) was used to evaluated the accuracy of the proposed method. Concordance of 99.6% for As and 98.3% for Pb were obtained. Certified reference material containing all elements studied was not found. The concentration of residual carbon in the samples after MIC was lower than 15 mg L-1 showing that the method was effective for flexible graphite digestion. Regarding the determination of analytes in samples, 4.3 ± 0.5 μg g-1 of Pb and 21.3 ± 0.1 μg g-1 of Zn were found in the flexible graphite "A" for the other samples "B", "C" and "D" all analytes were lower than the limit of quantification (LQ). These results showed that the samples of flexible graphite analyzed are in agreement with the limits recommended by the GE D5OYP12 and GE NEDC31735P which the maximum permissible concentration for each element is 200 μg g-1.